NATURAL RESOURCES OF CAPPARIS SPINOSA L. IN THE FERGANA REGION (Scientific journal of the Fergana State University, 2025)
The article presents data on the natural reserves of Capparis spinosa raw materials in the Fergana region. To determine natural, biological, and exploitable reserves, the methodology developed by Pupikina et al. (2019) was used. According to this methodology, in the accounting plots (10×10 m), the average number of total bushes is 20.58±1.21 pcs., the average number of mature bushes is 7.3±0.48 pcs., and the collection rate per plot is 1049.1±73.2 g. It was found that the yield of plant raw materials in the studied areas averages 61.37 kg/ha. As a result, in the Fergana region, the commercial area of the plant averages 95.0 hectares, and the volume of annual raw material procurement is 1.056 tons.